2022
DOI: 10.5603/ahp.a2022.2047
|View full text |Cite
|
Sign up to set email alerts
|

Real-life experiences of letermovir prophylaxis for cytomegalovirus infection in patients after hematopoietic stem cell transplantation: Polish Acute Leukemia Group (PALG) analysis

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…LMV is a drug that changes the paradigm of PET use in favor of prophylaxis as first-line management strategy against CMV [7,47,49]. A Polish experience with LMV prophylaxis, published recently, confirms its low toxicity with no myelosuppressive (or any other) adverse effect and good tolerability [50]. Our own experience with more than 30 patients treated with LMV seems to confirm its efficacy and safety (data not published).…”
Section: Post-transplantation Work-up and CMV Prophylaxismentioning
confidence: 75%
“…LMV is a drug that changes the paradigm of PET use in favor of prophylaxis as first-line management strategy against CMV [7,47,49]. A Polish experience with LMV prophylaxis, published recently, confirms its low toxicity with no myelosuppressive (or any other) adverse effect and good tolerability [50]. Our own experience with more than 30 patients treated with LMV seems to confirm its efficacy and safety (data not published).…”
Section: Post-transplantation Work-up and CMV Prophylaxismentioning
confidence: 75%
“…3 D ). Five and 1 studies, 52 respectively, were included for the analysis of CMV infection at any time after HSCT in adults and children, and the incidence of CMV infection at any time was 6% (95% CI, 3%–13%) in adults, which was comparable with that in children (20%, Fig. 3 E ).…”
Section: Resultsmentioning
confidence: 91%
“…Six studies including 1188 patients reported the incidence of CMV disease at 6 months after allo-HSCT. 29 32 , 45 , 52 The incidence of CMV disease at 6 months after allo-HSCT was 3% (95% CI, 1%–9%, Fig. 4 D ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cytomegalovirus (CMV) infection is a major complication after allogeneic hematopoietic cell transplantation (allo-HCT), and a serious trigger for other sequelae [1][2][3]. The introduction of letermovir into the prophylaxis of CMV infection has led to a large reduction of the CMV reactivation rate in seropositive adult patients after allo-HCT [4][5]. This effect obviously means fewer direct and indirect complications caused by the virus [6][7][8].…”
mentioning
confidence: 99%